Influencing mathematics students’ academic success through online intervention: A case study - Adamiak, J.P.; Sauls, R.D. (South African Journal of Higher Education, 2017)
Open distance learning (ODL), by the definition, subscribes to the limited direct engagement of the students with the learning institution. The University of South Africa, Western Cape, has placed key emphasis on providing an array of electronic support platforms to assist students with their needs in quantitative literacy skills. Consequently, as a part of this additional learning support, an online environment was designed in which the students, enrolled for various mathematics modules, were able to access an array of educational resources. Findings from similar studies suggest, that the utilisation of employment of additional learning support could show a positive effect on students’ academic achievement in distance learning. Therefore, a quasi-experimental research study was conducted to investigate this supposition by comparing the assessment outcomes among various student groups subjected to the additional learning support interventions. It has been found that online intervention might affect the success rate of the students, however, not necessarily in a simple or in the anticipated way.